KADERISASI PETUGAS IBADAT SABDA DI STASI SANTO FRANSISKUS ASISI TAWANG PAROKI HATI KUDUS TUHAN YESUS BATANG TARANG - Suryani, Ade Irma; Tinenti, Hemma Gregorius; Martinus, Martinus (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2025)
This study aims to examine the leadership formation process of Catholic Youth (OMK) as Word Worship officers and to identify the factors influencing their low level of participation in ministry at St. Francis of Assisi Tawang Station. This research employed a descriptive qualitative approach with OMK members and their instructors as the primary subjects. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, interpretation, and conclusion drawing. The findings show that the participation of Catholic Youth in church activities is generally positive, as most members are willing to serve when assigned as Word Worship officers. Their involvement includes roles such as leading the Word Worship, participating in liturgical celebrations, and contributing creatively to church life. However, their creativity and initiative remain limited, as many still rely on being appointed rather than volunteering for service. The main obstacles in the leadership formation process are the lack of professional mentors, such as catechists to accompany the youth, and internal challenges among OMK members, including low self-confidence and limited organizational skills. The study suggests that further research and pastoral attention are needed to strengthen the leadership formation and active participation of Catholic Youth in church ministries.